Depressive risk among Italian socioeconomically disadvantaged children and adolescents during COVID-19 pandemic: a cross-sectional online survey - Maria Serra; Anna Presicci; Luigi Quaranta; Maria Rosaria Erminia Urbano; Lucia Marzulli; Emilia Matera; Francesco Margari; Lucia Margari (BMC, 2022)
Abstract Background Children and adolescents and low-income individuals are considered particularly vulnerable for mental health implications during the current COVID-19 pandemic. Depression is a frequent negative emotional response during an epidemic outbreak and is also prone importantly to environmental risk like stressors derived from income inequality. We aimed to assess depressive symptomatology in a sample of Italian low-income minors during the COVID-19 outbreak. We hypothesized that the stronger were the negative effects of the pandemic on socioeconomic conditions, the higher would have been the risk for showing depressive symptoms. Methods We performed a cross-sectional study during July 2020, at the end of the Italian first wave of COVID-19 pandemic. We recruited 109 Italian socioeconomically disadvantaged children and adolescents from 7 to 17 years. We used an online survey to collect socio-demographic and clinical data and information about pandemic-related stressors and to assess depressive symptoms with the Children's Depression Inventory 2 (CDI 2), Parent Version (Emotional Problems subscale) and Self-Report Short Form. We performed logistic regression analysis to assess the association between depressive symptoms and potential risk factors for mental health. Results 22% and 14% of participants showed depressive symptoms at the CDI 2 Parent Version and Self-Report, respectively. Participants coming from families experiencing a lack of basic supplies during the pandemic (34.9%) were more expected to show depressive symptoms at CDI 2 Parent Version. Participants with a pre-existing neuropsychiatric diagnosis (26.6%) were more likely to exhibit depressive symptoms measured by CDI 2 Parent Version. Conclusions The results of our study showed that a group of Italian socioeconomically disadvantaged children and adolescents were more vulnerable to depressive symptoms if they suffered from a paucity of essential supplies during the pandemic or had pre-existing neurodevelopmental disorders. The promotion of educational and child-care programs and activities could be crucial in sustaining the prevention of mental distress in those frail subjects who particularly need support outside the family. Further studies are needed to detect effective preventive and therapeutic strategies to adopt promptly in the case of another pandemic wave.